How the biotin–streptavidin interaction was made even stronger: investigation via crystallography and a chimaeric tetramer - Chivers, Claire E. (Portland Press Ltd., 2011)
The interaction between SA (streptavidin) and biotin is one of the strongest non-covalent interactions in Nature. SA is a widely used tool and a paradigm for protein–ligand interactions. We previously developed a SA mutant, termed Tr (traptavidin), possessing a 10-fold lower off-rate for biotin, with increased mechanical and thermal stability. In the present study, we determined the crystal structures of apo-Tr and biotin–Tr at 1.5 Å resolution. In apo-SA the loop (L3/4), near biotin's valeryl tail, is typically disordered and open, but closes upon biotin binding. In contrast, L3/4 was shut in both apo-Tr and biotin–Tr. The reduced flexibility of L3/4 and decreased conformational change on biotin binding provide an explanation for Tr's reduced biotin off- and on-rates. L3/4 includes Ser(45), which forms a hydrogen bond to biotin consistently in Tr, but erratically in SA. Reduced breakage of the biotin–Ser(45) hydrogen bond in Tr is likely to inhibit the initiating event in biotin's dissociation pathway. We generated a Tr with a single biotin-binding site rather than four, which showed a simi-larly low off-rate, demonstrating that Tr's low off-rate was governed by intrasubunit effects. Understanding the structural features of this tenacious interaction may assist the design of even stronger affinity tags and inhibitors.